From taxonomic deflation to newly detected cryptic species: Hidden diversity in a widespread African squeaker catfish - Jirsová, Dagmar; Štefka, Jan; Blažek, Radim; Malala, John O; Lotuliakou, David E; Mahmoud, Zuheir N; Jirků, Miloslav (Scientific reports, 2019)
Cryptic genetic diversity and erroneous morphological species determination represent frequent problems in biodiversity research. Here, examination of 138 specimens of Synodontis (Mochokidae, Siluriformes) from the Nile River and Lake Turkana revealed the presence of both S. schall-like and S. frontosus-like morphotypes, with a phenotypic gradient between them. We concluded phylogenetic and population genetic analyses based on two mitochondrial and one nuclear marker including 131 coxI (565 bp), 96 cytb (973 bp) and 19 RAG2 (896 bp) sequences from the Nile-Turkana population, plus additional GenBank data of Synodontis spp. Whilst nuclear data were inconclusive, mitochondrial sequences suggested that both morphotypes and intermediate forms are conspecific. The results imply probable synonymy of S. frontosus with S. schall. Conversely, a strong biogeographical signal was revealed among widely distributed and supposedly conspecific S. schall-like catfish of the Nilo-Sudanian ichthyological province. Synodontis schall sensu stricto (=Eastern clade), as defined by type locality in the Nile, is apparently restricted to the eastern part of the Nilo-Sudanian ichthyological province (e.g. Nile, Turkana, Chad). Synodontis schall Western clade (Senegambia, Niger, Chad) most probably represents a cryptic taxon, unrecognized thus far due to the absence of distinctive morphological differences.
Keywords: Bayes Theorem; Bayesova věta; Genetics, Population; Cytochromes b; Catfishes; Electron Transport Complex IV; Haplotypes; Animals; haplotypy; sumci; respirační komplex IV; biodiverzita; populační genetika; Biodiversity; Phylogeny; zvířata; fylogeneze; cytochromy b